Thermal driven wavelength-selective optical switch based on magnetic polaritons coupling. (November 2020) - Guo, Yanming; Xiong, Bo; Shuai, Yong; Zhao, Junming
Highlights: The switching behavior of the wavelength-selective switch is opposite to the nature of VO2, and the tunability is over an order of magnitude during phase transition. The phenomenon of suppressed transmission is explained by the proposed magnetic polariton coupling mode and verified by current circuits. MP is excited to enhance transmission at metallic VO2, while MP coupling mode surpresses transmission at insulating VO2 . The switch still performs well at large oblique incidences and the resonant frequency does not change with incident angle. Abstract: A wavelength-selective optical switch by thermally controlling which has higher transmittance at metallic phase of Vanadium dioxide (VO2 ) and lower transmittance at insulating phase is presented. By skillfully designing the structure, magnetic polaritons (MPs) are excited to enhance transmission to 0.79 indicating "on" mode with VO2 at metallic phase. The coupling between two magnetic polariton modes is excited at the same frequency to suppress the transmittance peak to 0.045 indicating "off" mode with VO2 at insulating phase, demonstrating tunability by over an order of magnitude during phase transition. Magnetic polariton coupling mode is proposed to explain the phenomenon of surpressed transmission and the electromagnetic field distributions confirm it. The proposed optical switch still works well at a large oblique incidence and the resonant frequency does not change with the incident angle. Our study may benefit the microelectronics and infrared active filtering applications.